Potensi Cryptocurrency Dalam Inklusi Keuangan Islam Berkelanjutan - Satria Darma (Al Maal: Journal of Islamic Economics and Banking, 2022)
Cryptocurrencies have been gaining attention in the financial world in recent years, with the model reportedly being able to digitally transfer, store and record information, and has the potential to transform traditional financial services. Financial digitization is very much needed in today's conditions, where all life uses digital systems to support life. Financial modification is certainly needed in realizing sustainable finance, especially in the field of Islamic finance globally. In this study to explore the potential of cryptocurrencies in the inclusion of sustainable Islamic finance. This research was conducted using a library research model, with data collection in the form of books, journals, websites and other objects that are considered relevant and then carried out an in-depth study through descriptive qualitative analysis methods. The results of the study indicate that cryptocurrency is a financial digitization that has the potential to support and ensure that the Islamic financial transaction process can be accessed by millions of consumers so that the goal of financial inclusion can be achieved and supports the development of the financial industry that has transaction efficiency values so that it can realize sustainable Islamic finance.